THE IMPACT OF ACCOUNTING CONSULTING ON THE EFFICIENCY OF IT-SPHERE ENTERPRISES - Myronchuk, Zoriana; Tsitska, Nadia.Evgenivna; Andrushko, Ruslana; Maletska, Olga; Kolach, Svitlana (European Science, 2023)
The purpose of this scientific article is to systematically consider the essence and prospects of accounting consulting development in the context of enterprise management in the IT-sphere. In particular, the study is aimed at identifying the theoretical